2008
DOI: 10.1038/leu.2008.11
|View full text |Cite
|
Sign up to set email alerts
|

MDM2 antagonist nutlin-3 is a potent inducer of apoptosis in pediatric acute lymphoblastic leukemia cells with wild-type p53 and overexpression of MDM2

Abstract: In pediatric acute lymphoblastic leukemia (ALL), overexpression of murine double minute 2 (MDM2) protein by leukemic cells is typically associated with a wild-type (wt)-p53 phenotype and chemoresistance. A recently developed small-molecule antagonist of MDM2, nutlin-3, inhibits the MDM2-p53 interaction, resulting in induction of p53 activity and apoptosis. In this study, we evaluated the cytotoxic effect of nutlin-3 on ALL cells with different p53 status and MDM2 expression, using 18 cell lines and 30 primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
111
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(113 citation statements)
references
References 40 publications
2
111
0
Order By: Relevance
“…42 This finding is in agreement with other studies showing the importance of survivin downregulation in nutlin-3a-induced cell death in pediatric acute lymphoblastic leukaemia. 20 In this study, we verified the significance of the p53 mutation functionally at codon-215 of exon-6, AGT [Ser]4TGT [Cys], identified here in DEL cells. Earlier studies, by using gene reporter assays, have shown that this p53 mutation retains residual transactivation activity, including the target proapoptotic genes Bax and Puma, although its significance remained unknown.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…42 This finding is in agreement with other studies showing the importance of survivin downregulation in nutlin-3a-induced cell death in pediatric acute lymphoblastic leukaemia. 20 In this study, we verified the significance of the p53 mutation functionally at codon-215 of exon-6, AGT [Ser]4TGT [Cys], identified here in DEL cells. Earlier studies, by using gene reporter assays, have shown that this p53 mutation retains residual transactivation activity, including the target proapoptotic genes Bax and Puma, although its significance remained unknown.…”
Section: Discussionmentioning
confidence: 68%
“…[10][11][12] Accordingly, in vitro and in vivo studies have shown that inhibition of Mdm2, a critical negative regulator of p53, by using a recently developed small molecule, nutlin-3a, results in reactivation of the p53 pathway and significant antitumour activity in a variety of solid tumours and some haematologic malignancies harbouring a wild-type (wt) p53 gene. [13][14][15][16][17][18][19][20][21][22][23][24][25] We have shown earlier that most ALK þ ALCL tumours express p53 protein at variable levels and carry a wt p53 gene. 26 In this study, we hypothesized that inhibition of the Mdm2-p53 interaction would result in reactivation of the p53 pathway in ALK þ ALCL cells.…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that loss of p19 potentiated Nutlin‐3a‐induced growth inhibition of neuroblastoma cells 30. Further, MDM2 overexpression reportedly enhances cell sensitivity to Nutlin‐3a 31. We predict that the unique nature of each TP53 mutant ( e.g .…”
Section: Discussionmentioning
confidence: 80%
“…Thus, p53 is potentially an important target in the treatment of drug-resistant leukemia. [44][45][46] Leukemic stem cells are frequently drug resistant. [47][48][49] Our results point out that one of the first events involved in this process is decreased expression of the p53 tumor suppressor protein.…”
Section: Discussionmentioning
confidence: 99%